Animal feed market formation trends in Ukraine considering European integration processes - Vdovenko, Nataliia; Palamar, Irina; Fedyshko, Marina (Technology audit and production reserves, 2015)
The influence of transformation processes of reforming the agricultural sector and animal husbandry, which allow to increase production of grain products and animal feed was investigated in the paper. In addition, the evolutionary process of the animal feed market formation in Ukraine and the EU was analyzed. It was proved that the domestic animal feed market is characterized by the supply of domestic and foreign producers, creating tough competition due to the allocation of high-quality products and favorable price. Thus, the economic efficiency of animal feed enterprises depends on the state regulatory activity in the commodity market, specifically grain market. This specifics of functioning is formed by dynamics of animal feed imports to Ukraine, which in 2014 reached a maximum of 178,2 thousand tons, which is 31,61 % more than in 2010. Ukraine imported 86,9 thousand tons of wheat to the EU in an amount of 21,1 million Euros. Thus, by exporting grain products, comprising raw components for animal feed production, Ukraine holds import operations during which buys finished animal feed, which contains its own raw materials, but ready for feeding animals. Therefore, in the domestic market, with raw material resources available, there is an urgent need for high-tech production considering the safety and hygiene principles of animal feed. So, the problems of entry of the commodity group of animal feed to the EU market as a complete product for use by manufacturers in agricultural production are well founded. It was proposed to organize the system of production and circulation of animal feed, safety indicators of which meet the EU requirements and provide Ukrainian market operators with the opportunity to export feed to the EU Member States and other countries. It was proved that an effective measure is improving the legal protection of end users of feed and establishing clear responsibilities of market operators (feed labeling). Finally, developing the mechanism of recovery of animal feed producers from the crisis based on the preservation of the functioning principles of the national animal feed market harmonized with the EU legislation and adoption of the Law of Ukraine "On feed" were proposed.